Person–Job Fit and Innovation Behavior: Roles of Job Involvement and Career Commitment - Huang, Wenyuan; Yuan, Chuqin; Li, Min (Frontiers in Psychology, 2019)
This study examines the effect of person–job fit on innovation behavior, highlighting the mediating role of job involvement and the moderating role of career commitment in this relationship. We tested our hypotheses using a sample of 474 employees from 30 IT enterprises in China’s Pearl River Delta region. The results reveal that person–job fit influences innovation behavior by enhancing job involvement. In addition, career commitment strengthens the positive influence of person–job fit on both job involvement and innovation behavior. These findings are consistent with person–environment fit theory and identity theory. This research increases understanding of how person–job fit influences innovation behavior via job involvement and career commitment. Implications and managerial practice are also discussed at the end of the research.